Parasites et parasitoses des poissons - de Kinkelin, Pierre (éditions Quae, 2014)
This richly-illustrated work offers a representative panorama of parasitic agents encountered in fish. Based on the new phylogenetic classification concepts, it emphasises the biological properties, epidemiology and clinical effects of groups of organisms in question, in the light of cognitive advances made possible by the new biology tools. It is intended for a wide audience, from the world of aquaculture to animal health and teaching as well as to researchers.